Error Analysis of English Language: A Study of Mara Students of Class X - Eliyas, D (JOURNAL OF INDIAN EDUCATION, 2011)
The paper attempts to observe and analyse the errors of the Mara learners of English in the context of second language learning situation at Class-X level in the schools of Maraland, Saiha District, Mizoram. The sample consisted of 350 students (183 boys and 167 girls) randomly selected from 607 Mara students from 24 randomly selected High schools of Saiha District, Mizoram. To identify the areas where the Mara students face problems in discourse, a free composition on ‘The Christmas’ was administered. The identified errors were noted on the margin of the answer scripts and then tabulated under broad categories as tense, preposition, article etc. Findings related to errors committed by students studying in different types of schools, schools in rural and urban area etc. were compared and sources of the errors were found out. Remedial strategies were also suggested on the basis of the findings.